Generation of Human Ventral Midbrain Organoids Derived from Pluripotent Stem Cells. Issue 9 (19th September 2022) - Sozzi, Edoardo; Nilsson, Fredrik; Kajtez, Janko; Parmar, Malin; Fiorenzano, Alessandro
Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide and is caused by the degeneration and loss of dopamine (DA) neurons in the ventral midbrain (VM). The focal and progressive degeneration of DA neurons in the VM makes PD a particularly attractive target for cell‐based therapies. Human pluripotent stem cells (hPSCs) offer unprecedented opportunities to model the development and functional properties of human DA neurons in a dish. The use of human in vitro models based on hPSCs has empowered studies of VM development and provided access to neurons expressing a particular disease‐specific phenotype. Currently, hPSC differentiation is most routinely carried out in monolayer cultures, which do not properly recapitulate cell‐cell interactions and the structural complexity of the brain. Moreover, 2D cultures are challenging to maintain long term, as the cells tend to detach from the plate and lose their functional characteristics. This precludes the possibility of mimicking later phases of DA neurogenesis and recreating the complexity of functional neural circuitries. Here, we describe protocols showing how to maintain hPSCs in an undifferentiated state and how to then drive these hPSCs into 3D regionalized VM organoids. After long‐term culture, these VM organoids exhibit mature and post‐mitotic molecular features, including neuromelanin pigments similar to those released in primate VMs. We also report a protocol describing how to efficiently perform immunohistochemistry and how to detect neuromelanin‐containing DA neurons in VM organoids. Together, these protocols provide a 3D in vitro platform that can be used to better understand the molecular mechanisms underlying DA neuron function and disease and may serve as a powerful tool for designing more targeted disease‐modifying therapies. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Human pluripotent stem cell culture Basic Protocol 2 : hPS cell differentiation for the generation of human ventral midbrain organoids Basic Protocol 3 : Characterization of ventral midbrain organoids